ROBOTACK-O-MOS: ROBOT ATTACK MOSQUITOS, INOVASI ALAT PENGUSIR NYAMUK PORTABLE BERBASIS ULTRASONIC WAVE DAN AUTO-ROTATE DEVICE - Wigiardi, Agus; Pradana, Aditya Doni; Budiasih, Diah; Puspitarini, Dwi Yuni; Prabantara, Saprindo Harun (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Incidences of diseases caused by mosquitos have been widely reported. Malaria, dengue and chikungunya are still being scourges to people in tropical countries. Many prevention actions have done to push down the number of those incidence. This study used ultrasonic wave as a newest technology to attack mosquitos. The purpose of the study was to make a repellent based on ultrasonic wave and auto rotate device with fully portable technology and combined with ethnical culture of Yogyakarta. The process of making those repellent is literature review, made a design, followed by processing the hardware and software, finishing, and evaluation